Criminal evidence : from crime scene to courtroom - Regensburger, Derek, 1970- (Frederick, MD : Aspen Publishing, 2023)
'Text on criminal evidence for use in college courses'--
Introduction to evidence and the rules of evidence -- The criminal justice process -- Basic evidentiary terms : relevance, burden of proof, and circumstantial evidence -- Physical evidence -- Identification evidence -- Confessions -- Pretrial discovery -- The exclusionary rule and motions to suppress evidence -- Witnesses part I : expert and lay witnesses -- Witnesses part II : reliability of forensic evidence -- Witnesses part III : competency and privilege -- Witnesses part IV : impeachment and cross-examination -- Character evidence -- Hearsay evidence -- Authentication of evidence and the best evidence rule.
Includes bibliographical references and index.
Buku bacaan asas Sains Forensik.
Keywords: Evidence, Criminal -- United States